Factors influencing the adoption of ICT tools in Kerala marine fisheries sector: an analytic hierarchy process approach. Issue 7 (3rd July 2018) - Sabu, M.; Shaijumon, C. S.; Rajesh, R.
ABSTRACT: Adoption of a new ICT tool in the fisheries sector depends on several factors such as ease of use, affordable cost, information, and time. All these factors determine the preference of an existing tool over others for productivity enhancement. Which ICT tool is more beneficial than others is a continuing debate among researchers. However, the literature currently lacks detailed studies of fishermen criteria for selecting the best ICT tools in the marine fisheries sector. This paper is based on a framework which explains the factors influencing the adoption of ICT tools for the better fish catch, with the help of a multi-criteria decision making approach, called Analytic Hierarchy Process. Also, in the study we have compared the results of analysis using AHP with popular method TOPSIS and the obtained results were validated. The Study also assesses scientifically, which is the most important ICT tool for fishing through a case study in Northern and Southern parts of Kerala, a state in the southern India. The Study finds that Global Positioning System (GPS) is the most beneficial and important ICT tool in marine fishing. In contrast to the earlier studies, the results show that wireless set is important than other tools like mobile phone and echo-sounder for multi-day fishing. The cost-benefit analysis also supports findings of the study.